Facet tropism: Association between cervical disc degeneration and cervical spondylotic radiculopathy in middle-aged patients. (May 2022) - Zhou, Yuanxing; Wang, Bo; Pei, Zhongyu; Yang, Jun; Jiang, Chang; Tian, Xiliang; Qu, Xiaochen; Li, Linan
Highlights: Cervical spondylotic radiculopathy; Facet joint; Facet tropism (FT); Risk factor; Disc degeneration. Abstract: This study aimed to retrospectively explore the relationship between facet tropism (FT) and cervical disc degeneration in cervical spondylotic radiculopathy (CSR) patients on 3-dimensional views. A total of 180 middle-aged patients with single-level CSR at C4/5 who underwent cervical CT and MRI in our hospital were included. The incidence of FT (or called FT (+), defined as FT ≥ 7 degree) at C3/4, C4/5, C5/6 levels were measured and calculated by reconstructed CT images on 3-dimensional views. The grade of cervical disc degeneration at three levels was assessed by MRI images by the method of Miyazali. Univariate analysis was performed to compare their cervical disc degeneration grade and CSR incidence between two groups stratified by FT (+). Moreover, a logistic regression model was used to investigate the association between FT (+) and grade of cervical disc degeneration and incidence of CSR adjusting for age, gender, and BMI. Grade of cervical disc degeneration and incidence of CSR in axial FT (+) group were both significantly increased compared to axial FT (-) group, while sagittal and coronal FT (+) groups showed no difference. Axial FT (+) was significantly associated with the grade of cervical disc degeneration and incidence of CSR. in middle-aged patients with CSR, axial FT (+) might be the risk factor for cervical disc degeneration but not sagittal and coronal FT (+). Also, axial FT (+) was positively associated with CSR incidence. Therefore, axial FT might play a vital role in the progression of cervical disc degeneration and CSR occurrence.